اسلام میں ماں کا مرتبہ: احسان دانش کی نظم "گورستان" کا مطالعہ: Dignity of Mother in Islam: A Study of Ehsaan Dānish’s Poem “Goristān” (Al-Qamar, 2023)
In Islam, mothers hold a position of immense importance and are accorded great respect and honor. The teaching of Islam emphasize the significance of mothers and highlight their invaluable contributions to society, the family unit, and the upbringing of children. Mothers play a vital role in the education and upbringing of their children. Islam emphasizes the importance of instilling good values, morals, and religious teachings in children. A mother is often the primary source of emotional support for her children. Islam encourages mothers to provide a nurturing and loving environment for their children, offering them comfort and solace. The Prophet Muhammad ﷺ showed affection and compassion to his own children, setting an example for all parents. Ehsan Danish was a prominent Urdu poet, prose writer, linguist and scholar from Pakistan. Ehsan had an extraordinary attachment to his mother. After 1940, Ehsan Danish's mother died in Lahore. In memory of his mother, he wrote a long poem, The Goristan, which was published in 1941. The poem covers topics such as pain and suffering, instability of the world, helplessness of man, death and annihilation, place of learning, etc. This article presents a critical overview of this poem.
Keywords: Ahsan Danish; Financial condition of poet; Sacrifices of poet’s mother; intellectual review of the poem; technical review of the poem